Al-Hawā wa Al-Syahwah Fī Al-Qur’ān Al-Karīm: Dirāsah Dalāliyyah - Ahmad Suharto; Pamasa Ardana; Intan Pratiwi Mustikasari; Muhammad Badrun (Studia Quranika, 2024)
There is disagreement among scholars since the word "Qur'an" has multiple meanings. The Qur'anic phrases "Al-Hawa" and "Al-Syahwah" are examples of pairs of synonymous sentences. At first glance, from the perspective of the second language, the lafadz has almost the same meaning, namely love or pleasure. But the Qur'an gives different meanings from the two lafazh. This study aims to find out the original meaning of lafazh Al-Hawa and Al-Syahwah, find out the difference in meaning by examining the contextual meaning of lafazh Al-Hawa and Al-Syahwah in the Qur'an, to reveal the wisdom contained in the Qur'an as a whole. To examine the differences between the words Al-Hawa and Al-Syahwah in the Qur'an, the author uses a descriptive-analysis method and a semantic approach, namely by examining the words Al-Hawa and Al-Syahwah in terms of linguistic differences. From linguistic differences, it can be concluded that al-Hawa is more inclined to opinions or beliefs that are inclined to negative traits because they neglect the perpetrators. While al-Syahwah is more inclined to the senses that have no effect on the body but affect psychological pleasure that is praiseworthy at one time and can be reprehensible at another time